Sustainability Ethics of Safety in the Building Maintenance Industry: Technical Manager’s Perspectives - Diyana, Kamarudin; Mohammad Affendy, Omardin (KnE Social Sciences, 2019)
Building maintenance (BM) projects usually involve various technical individuals such as building managers, architects, and building contractors. These individuals are usually concerned with certain issues pertaining to their views and experiences on a range of ethical topics surrounding BM industry activities. The issue of professional ethics plays an important role in quality-related problems in a BM project. Ethics is a vital component in producing a profitable long-term profit in the BM industry. This paper highlights the process practice of professional ethics and sustainability in the BM industry and how ethics influences the activities of BM projects. This qualitative case study recruited four (4) technical managers within the BM organisations. Data for this research were collected through semi-structured interviews with technical managers of the BM organisations. Results indicated that different types of unethical conducts impact BM tasks significantly. This study found that it is important to include professional ethics as a pre-requisite to attaining sustained and acceptable quality in BM. The study also suggests several approaches and methods enhance professionalism among BM professionals, which could help improve the quality in BM projects. The findings provide safety sustainability ethics process to BM organisation on how to address the ethical root issues when confronting the Malaysian BM industry.